PENGEMBANGAN PERANGKAT KERAS SISTEM MITIGASI DAN PEMANTAUAN BANJIR TERPADU MENGGUNAKAN SENSOR FUSSION - Dicky Kurniawan; Agus Mulyana (INFOKOM (Informatika & Komputer), 2020)
Flooding becomes a problem when the rainy season arrives. The impact caused not only by a pool of water, damage to infrastructure, and interrupted access to land transportation, to fatalities caused by electric shocks, flood currents, even post-flood diseases. With the impact caused by flooding, we need a device for monitoring the level of water leveling the river and can work optimally in every weather condition, environmental conditions. So the research was made with a field specification that is able to answer all the problems that occur with the previous tool, namely the Design of Android-Based Integrated Flood Monitoring System and Website with the HTTP Request communication protocol. This research is a device development by applying Fussion Sensor which combines several sensors such as ultrasonic sensors, BME280 sensors and rain sensors with the incorporation of these sensors with the aim of increasing accuracy in reading data by comparing water level data with weather conditions with reference to sensor comparison data from BMKG, BPS Bandung as data validation. Application of the MQTT communication protocol to support data transmission from the Fussion Sensor. With this renewal research, it is hoped that it will be beneficial for the people and government in dealing with flood preparedness, especially in the city of Bandung.